Occurrence of aflatoxin M1 in raw, pasteurized, UHT cows' milk, and dairy products in Lebanon. (May 2020) - Daou, Rouaa; Afif, Charbel; Joubrane, Karine; Khabbaz, Lydia Rabbaa; Maroun, Richard; Ismail, Ali; Khoury, André El
Abstract: In this study, a total amount of 868 samples of raw cows' milk, pasteurized and UHT cows' milk, and dairy products were analyzed for their AFM1 content. Milk and dairy consumption in Lebanon was evaluated through a food frequency questionnaire, and accordingly the exposure to AFM1 and its association with liver cancer risk in Lebanese population were evaluated. Results showed contamination in raw milk, pasteurized and UHT milk, and dairy products at a range of 0.011–0.440 μg/l, 0.013–0.219 μg/L, and 0.015–7.350 μg/L respectively; with 28%, 54.5%, and 45.5% respectively of samples with AFM1 above maximum tolerable limit (MTL) set by the European Commission. AFM1 consumption was shown to be associated with 0.0041 additional cancer cases per 100, 000 persons per year. Based on these results, milk and dairy consumption in Lebanon can be considered hazardous and may present a significant risk on the health of the Lebanese population especially children. Highlights: 868 samples of cows' milk and dairy products were collected. Random sample selected from Lebanon to participate in food frequency questionnaire. Immunoaffinity columns used for AFM1 purification and HPLC-FLD for quantification. High AFM1 contamination levels in raw, pasteurized, and UHT milk and dairy products.